PRODUCT DEVELOPMENT ASSISTANCE TO IMPROVE THE ECONOMY OF MSMES IN SUGIHMUKTI VILLAGE, PASIRJAMBU DISTRICT - Nasution, Ade Iskandar; Nur'aeni, Nur'aeni; Mintarsih, Mimin; Setiawan, Topan; A . S, Nabi Muhammad; Alifiah, Salma (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
In Sugihmukti Village, Pasirjambu District, the majority of the community relies on agriculture, plantations, and home-based businesses that produce various local products, including processed foods, traditional beverages, and handicrafts. This potential should be able to drive the village's economy; however, in practice, there are still various obstacles. Therefore, assistance in product development is needed to enhance the economy of MSMEs in Sugihmukti Village. The method used in this service is Oriented-Project Planning (OPP), where the implementation of the service focuses on planning development and executing programs to achieve specific goals. The stages of implementation in this service include the stages of socialization, training, technology application, mentoring, evaluation, and program sustainability. The results of the activities indicate that this program successfully enhanced the capacity of business actors through training, technology application, and more effective marketing strategies, resulting in products that are more innovative, of higher quality, and competitive; the positive impacts are evident from the increased market opportunities, strengthened cooperation networks, and the commitment to program sustainability that supports the continuous economic growth of the village.